PERMANENT MANDIBULAR CANINE WITH TWO ROOTS AND TWO CANALS - AIN , QU; AZAM , S; BAIG , I (Biological and Clinical Sciences Research Journal, 2024)
Mandibular canines are documented as frequently having one root and one canal in most cases, although around 15% may have two canals and two roots. Thus, anatomic variation exists therefore knowledge and keen observation during root canal can help to identify the less frequent variation morphology of tooth and play a pivotal role in the success of root canal treatment. This case report discusses a mandibular canine with two roots and two canals.